Kualitas Pelayanan Publik Berbasis E-Government di Kecamatan Mojolaban, Kabupaten Sukoharjo Provinsi Jawa Tengah - Alhanif Islamudin, Rozzaq; Siti Aisyah; Ida Zubaidah (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the quality of e-Government-based public services in Mojolaban District, Sukoharjo Regency, Central Java Province. The study used a descriptive qualitative method, with data collection techniques through interviews, observation, and documentation. The results indicate that the implementation of e-Government through the Digital Population Identity (IKD) system can improve the efficiency, transparency, and accuracy of public services. However, obstacles remain, including limited network infrastructure, low digital literacy, and poor system integration between agencies. In conclusion, the implementation of e-Government in Mojolaban District has improved the quality of public services, although human resource capacity building and technological infrastructure strengthening are needed to optimize and sustain services.   Keywords: E-Government, Public Services, Service Quality, Administrative Digitalization